Предмет: Математика, автор: Keha59

Нужно упростить выражение

Приложения:

Ответы

Автор ответа: Lemon4iki
0
(frac{m^2-3m+9}{9m^2-1}*frac{3m^2+m}{m^3+27}-frac{m+3}{3m^2-m}):frac{5}{m^2+3m}-frac{15m+6}{5-15m}=\
=(frac{m^2-3m+9}{(3m-1)(3m+1)}*frac{m(3m+1)}{(m+3)(m^2-3m+9)}-frac{m+3}{m(3m-1)})*frac{m(m+3)}{5}-frac{15m+6}{5(1-3m)}=\
=(frac{m}{3m-1}-frac{m+3}{m(3m-1)})*frac{m(m+3)}{5}-frac{15m+6}{5(1-3m)}=\=
frac{m^2-m-3}{m(3m-1)}*frac{m(m+3)}{5}+frac{15m+6}{5(3m-1)}=\=
frac{(m^2-m+3)(m+3)}{5(3m-1)}+frac{15m+6}{5(3m-1)}=frac{m^3+3m^2-m^2-3m+3m+9+15m+6}{5(3m-1)}=\=
frac{m^3+2m^2+15m+15}{5(3m-1)}=frac{m(m^2+2)+15(m+1)}{5(3m-1)}
Похожие вопросы
Предмет: Английский язык, автор: elizavetazirkova804